OP poisoning in Children a review - Shrestha, Sitaram (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Poisoning is a relatively important health problem among children. Each year around the world approximately two million children under the age of five are poisoned. Children are adventurous and inquisitive, hence the high incidence of poisoning being recorded during their developmental period. The majority of poisoning cases are involuntary and inadvertent. Children may be victim of different types f poisoning and among them organophosphorous compound poisoning is in our day to day practice. Organophosphorous compounds which are available in different forms and used as agricultural and household insecticides and in the treatment of animal ectoparasites and human lice infestation. These substances are absorbed via the lungs, skin and the alimentary tract. Food including stored grains contaminated by a spray of these insecticides had been known to cause severe poisoning. This review article will remind the history of OP poisoning in short and will discuss about the classification of poisoning according to the toxicity of the compounds. Further it will discuss about the clinical features of this poisoning and lastly briefly talk about its management.